Verifikasi–Diseminasi Manajemen Komunikasi Lintas Sektor dan Peran Manajemen SDM dalam Kesiapsiagaan Bencana Pangandaran - Taqwa Putra Budi Purnomo Sidi Hiram; Justin Bongsoikrama (Jurnal Komunikasi Nusantara, 2026)
Pangandaran Regency faces a high threat of coastal disasters, but preparedness remains vulnerable when information comes in very quickly, from multiple sources, and is not always verified, making cross-sector coordination difficult. This study analyzes cross-sector communication management in the information verification-dissemination process and the role of human resource management, which includes role distribution, competencies, capacity building, work coordination, and quality control. The study uses a qualitative case study approach with in-depth interviews, limited observation, and document study; informants were selected purposively and developed using snowball sampling until data saturation was reached. The data were analyzed using Miles' model through data condensation (hybrid coding), data presentation (matrix/networking and process tracing), and conclusion drawing verified through triangulation, brief member checking, and audit trails. The findings show that the flow of reports from citizens and social media triggered overload, making layered verification a critical point; BPBD, Basarnas, Polri, and volunteers played different roles with Pusdalops as the control node. Dissemination became effective when the release authority was locked, messages were standardized, and corrections were made quickly when hoaxes appeared. Quality control is marked by the use of internal validity indicators and status determination coordination meetings, which maintain narrative consistency and accelerate community action directives across various communication channels. In conclusion, preparedness is strengthened when the verification-dissemination process is orderly and supported by competent and well-managed human resources during information surges. Abstrak Kabupaten Pangandaran menghadapi ancaman bencana pesisir yang tinggi, tetapi penguatan kesiapsiagaan masih rentan ketika informasi masuk sangat cepat, berlapis sumber, dan tidak selalu terverifikasi sehingga koordinasi lintas sektor mudah tersendat. Penelitian ini menganalisis manajemen komunikasi lintas sektor pada alur verifikasi–diseminasi informasi serta peran manajemen SDM yang mencakup pembagian peran, kompetensi, penguatan kapasitas, koordinasi kerja, dan kontrol mutu. Penelitian menggunakan pendekatan kualitatif studi kasus dengan wawancara mendalam, observasi terbatas, dan studi dokumen; informan dipilih secara purposive dan dikembangkan secara snowball hingga kejenuhan data. Data dianalisis dengan model Miles melalui kondensasi data (hybrid coding), penyajian data (matriks/jejaring dan process tracing), serta penarikan kesimpulan yang diverifikasi melalui triangulasi, member checking ringkas, dan audit trail. Temuan menunjukkan arus laporan warga dan media sosial memicu overload, sehingga verifikasi berlapis menjadi titik kritis; BPBD, Basarnas, Polri, dan relawan menjalankan peran berbeda dengan Pusdalops sebagai simpul kendali. Diseminasi menjadi efektif ketika otoritas rilis dikunci, pesan distandarkan, dan ralat dilakukan cepat saat hoaks muncul. Pengendalian mutu ditandai penggunaan indikator validitas internal dan rapat koordinasi penetapan status, yang menjaga konsistensi narasi dan mempercepat arahan tindakan masyarakat di berbagai kanal komunikasi. Kesimpulannya, kesiapsiagaan menguat bila proses verifikasi–diseminasi tertib dan ditopang SDM yang kompeten serta terkelola pada lonjakan informasi.